ANY CYCLIC QUADRILATERAL CAN BE INSCRIBED IN ANY CLOSED CONVEX SMOOTH CURVE. (31st May 2018) - AKOPYAN, ARSENIY; AVVAKUMOV, SERGEY
Abstract : We prove that any cyclic quadrilateral can be inscribed in any closed convex $C^{1}$ -curve. The smoothness condition is not required if the quadrilateral is a rectangle.